024 Electronic intervention to improve acute neurology referral system. Issue 12 (14th November 2019) - Routledge, Emma; Ziff, Oliver; Jarman, Paul; Turner, Chris; Chandratheva, Arvind
Abstract : Introduction: There is conflicting viewpoints regarding phone versus email referral systems within acute neurology. Methods: Our study evaluates the referrals system at University College London Hospital. We assessed how effective the pre-existing phone system was at managing referrals and compared this to a newly implemented email system. Over a month period the neurology phone call-log was interrogated. We recorded incoming and outgoing calls (missed and received), timing and call duration. After the email system was implemented, we assessed the email-logs over a month period. Results: With the phone system nighty nine incoming and 54 outgoing calls were recorded. Of these, 63% incoming calls were missed and 37% outgoing calls were not answered. Fridays were the busiest day of the week with 33% of the total calls (6% Mondays, 22% Tuesdays, 20% Wednesday, 19% Thursday). Most calls were received between 09:00 – 10:00 (25% of total) & 16:00 – 17:00 (22% of total). With the email system, 45 referrals were received electronically. Of these, all were responded to within 24 hours. Conclusions: The phone referral system was not fit for purpose with 63% of incoming calls missed. The electronic system was associated with far-reaching improvements in managing referrals.